A case report of changes in asymmetric colour use in paintings produced over 3 years post-stroke by a patient with spatial neglect - Gilles Rode; Eric Chabanat; Marine Lunven; Juliette Courtille; Patrice Revol; Karen T. Reilly; Laure Pisella; Yves Rossetti (Communications Psychology)
Abstract The most striking pathological manifestation of spatial cognition is visuospatial neglect in which patients omit contralesional stimuli by failing to process important features on the left side of visual or mental scenes. Despite decades of extensive neuropsychological exploration, this syndrome has still not revealed all its mysteries. Here we present the case of a person with visuospatial neglect who spontaneously produced 40 paintings in the 3 years following his stroke. By analysing the spatial distribution of colour entropy in these paintings over the course of recovery we found that these paintings contain perturbations that include changes in colour use. This approach, borrowed from statistical physics and information theory, revealed left-right asymmetries in boundary line length of monochromatic patches as well as in colour components. While the unpainted canvas surface disappeared as soon as 26 weeks post-stroke, left-right colour patch asymmetries displayed a slower recovery over one hundred weeks. Several hypotheses that can be tested in future research emerged from this study, including the possibility that these phenomenological findings demonstrate several distinct recovery mechanisms at work.